Oil price shocks and green bonds: A longitudinal multilevel model - Dina Azhgaliyeva; Ranjeeta Mishra; Zhanna Kapsalyamova (Asian Development Bank Institute (ADBI), 2021)
This paper contributes to the existing literature by investigating the impacts of crude oil price shocks on financial markets through an examination of the effect of oil price shocks on green bond issuance. Green bond issuance has been growing fast over the past several years; despite this, the share of green bonds in the total bonds remains small. Using the multilevel longitudinal random intercept and random coefficient models, this study investigates the effect of disentangled crude oil price shocks on green bond issuance in the private sector. Unlike the general bond market, our empirical analysis finds that oil supply shocks affect green bond issuance positively. We also find that the public issuance of sovereign green bonds tends to promote the private issuance of green bonds. Our results are robust and hold when using alternative models; they also survive a range of robustness tests.
Keywords: Q28; Q42; Q48; G23; 330; green bonds; sovereign bonds; green finance; oil shock; policy support; crude oil price